Reliability and sensitivity analysis of a retrial machine repair problem with warm standbys and imperfect coverage. Issue 2 (2nd April 2020) - Chen, Wu-Lin; Wang, Kuo-Hsiung
Abstract : This study aims at proposing system reliability and sensitivity analysis of a retrial machine repair problem with warm standbys and imperfect coverage. When an operating or warm standby machine fails, it may be immediately detected, located, and replaced with a coverage probability q by a standby if one is available. The Laplace transform technique is adopted to derive two system performance measures, system reliability and mean time to system failure ( MTTF ). Sensitivity analysis and relative sensitivity are then executed. In order to realize how each system parameter affects performance measures, extensive numerical experiments are designed and the important results are outlined. The results of this study provide a valuable reference for the good design of related real world systems.